Pendampingan Calon Guru Madrasah Diniyah Wali Songo Paciran Lamongan Melalui Kursus Kilat Kitab Shohih Bukhori - Abdul Mun'im; Muhyidin Muhyidin; M. Fathor Rohman (KERIS : Journal of Community Engagement, 2021)
Assistance for prospective madrasah diniyah teachers is part of the process of preparing cadres in Islamic symbols in the archipelago of the Republic of Indonesia. The mentoring that was carried out within a period of 1 month has inspired the students who have studied at the Madrasah Pondok Pesantren Sunan Drajat Lamongan. Learning through the sorogan, bandongan and batsul masa'il approaches is not just classical learning, but a lot of philosophical principles are obtained in the formation of the souls of students who are polite, tawadu' and have good character. Mentoring which aims to equip prospective madrasah diniyah teachers in both material and religious abilities also equips prospective teachers to have an educator spirit in conveying knowledge in the community. Ability testing is carried out in the sorogan, bandongan and discussion method approaches or better known as batsul masa'il. The results obtained in the mentoring activity are that prospective students have met the standards both in the ability to read the salafi book and the ability to convey the contents contained in the yellow book. The ability to study and read the yellow book is a must for every santri who will serve as a madrasah diniyah teacher.